Thermal analysis for axisymmetric stagnation point flow of viscoelastic magnetised nanofluid over a lubricated disk. Issue 1 (31st December 2022) - Abbasi, Aamar; Mabood, F.; Farooq, Waseh; Hussain, Z.
Abstract : This numerical study elaborates on the impacts of non-linear thermal radiation, Ohmic heating quadratic chemical reaction, an applied magnetic field on thermal characteristics of an axisymmetric flow of viscoelastic fluid in the vicinity of the axisymmetric stagnation point of a lubricated disk. The phenomena of the Brownian motion and thermophoresis with zero mass flux condition are also taken into account. The similarity transformation is used to reduce the number of independent variables in governing boundary layer equations and the transformed system of boundary value problem is solved using the box method. Variation in axial velocity, temperature and concentration profiles for various involved parameters of interest are graphically presented and categorically discussed. The local Nusselt number is documented for linear and non-linear radiations, whereas the Sherwood number is presented for linear and quadratic chemical reactions. It is observed that lubrication enhance both heat and mass transfer rates.